Penyusunan Strategi Pemasaran Islam dalam Berwirausaha di Sektor Ekonomi Kreatif Pada Masa Pandemi Covid-19 - Abdi, Moh Khoiri; Febriyanti, Novi (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2020)
Abstract: In the middle of the development of UMKMs that were not too good in early 2020, UMKMs in Indonesia were again tested with the Covid-19 outbreak in the middle of the Indonesian people. The spread of the Covid-19 virus has a direct impact on the drastic decline in the economy of UMKMs, because every citizen, even school students, has a day off to stay at home, as a result, UMKM companies are hampered in sales and production. This article intends to analyze how the preparation of a Islamic marketing strategy that can be done during the Covid-19 pandemic and supporting factors in entrepreneurship in the creative economy sector during the Covid-19 pandemic. Using qualitative research methods with a library research approach. The results of this study prove that the preparation of a Islamic marketing strategy in entrepreneurship in the creative economy sector can be planned through STP (Segmenting, Targetting and Positioning) to attract consumers with the concept of halal market, namely halal activist, active customers, and passive customers. While the supporting factors in entrepreneurship in the creative economy sector during the Covid-19 pandemic to run effectively and efficiently include the concept of promotion, service excellet customer rewards, affiliations or partnerships and social capital. Keywords: Islamic Marketing Strategy, Business, Creative Economy. Abstrak: Di tengah perkembangan Usaha Mikro Kecil Menengah (UMKM) yang belum terlalu baik di awal tahun 2020, UMKM di Indonesia kembali diuji dengan wabah Covid-19 ditengah masyarakat Indonesia. Penyebaran virus Covid-19 memberikan dampak yang berimbas langsung terhadap penurunan secara drastis ekonomi UMKM, karena setiap warga bahkan murid sekolah pun diliburkan agar tetap berada didalam rumah, akibatnya perusahaan UMKM terhambat dalam penjualan dan juga produksi. Artikel ini bermaksud ingin menganalisis bagaimana penyusunan strategi pemasaran Islam yang dapat dilakukan pada masa pandemi Covid-19 dan faktor pendukung dalam berwirausaha di sektor ekonomi kreatif pada masa pandemi Covid-19. Menggunakan metode penelitian kualitatif dengan pendekatan library research. Hasil penelitian ini membuktikan bahwa penyusunan strategi pemasaran dalam berwirausaha pada sektor ekonomi kreatif dapat direncanakan melalui STP (Segmenting, Targetting dan Positioning) untuk menarik konsumen dengan konsep halal market, yaitu halal activist, active customers, dan passive customers. Sedangkan faktor pendukung dalam berwirausaha di sektor ekonomi kreatif pada masa pandemi Covid-19 agar berjalan secara efektif dan efisien diantaranya adalah konsep promotion, service excellet customers rewards, afiliasi atau kemitraan dan modal sosial. Kata Kunci: Strategi Pemasaran Islam, Bisnis, Ekonomi Kreatif